Practice Guidelines for Clinical Pharmacists in Middle to Low Income Countries - Bronkhorst, Elmien; Gous, Andries G. S.; Schellack, Natalie (Frontiers in Pharmacology, 2020)
The profession of pharmacy is maturing as a clinical profession in South Africa and has experienced significant development over the past 10 years. The development of clinical pharmacy in Southern Africa started in the late 1980s. The Director-General of Health and Welfare requested an expansion of the pharmacist’s role in Southern Africa, in 1988, when he challenged pharmacists to be “more than just dispensers.” South Africa experience human resource challenges in terms of healthcare service delivery and the shortage of pharmacists has been acknowledged. Due to the human resource shortage, it is very difficult to allocate pharmacists to work in a clinical unit on a daily basis. This document serves to set out practice guidelines for clinical pharmacy in South Africa, and to indicate areas where clinical pharmacist should concentrate to build practice.